The Extent, Nature and Contributing Factors of Violence Against Iranian Emergency Medical Technicians - Soheili; Feizi; Rahmani; Parizad; Sheykh-Kanlou (Kashan University of Medical Sciences, 2016)
Background Workplace Violence (WPV) is one of the most complex and dangerous occupational hazards faced by pre-hospital emergency medical technicians (EMTs). Objectives This study aimed to assess the extent, nature and contributing factors of WPV against EMTs in Urmia, Iran. Materials and Methods A cross-sectional study was conducted on 120 EMTs from April to October 2014. A questionnaire was used for collecting the data. Descriptive statistics were applied to the data. Results Most of the participants (79%) experienced WPV during the past six months. Accident scene was the most important place of violence and the patients' companions were the main perpetrators of violence. Overall, 76% of violence victims reported "lack of awareness of the EMTs' duties" as the most important contributing factor for WPV. Conclusions This study highlighted the high frequency of WPV against EMTs. Evidently, the health care systems' officials would benefit from taking proper actions in this area, particularly by "staff and public education".